ChemInform Abstract: A Rapid Entry to Diverse γ‐Ylidenetetronate Derivatives Through Regioselective Bromination of Tetronic Acid Derived γ‐Lactones and Metal‐Catalyzed Postfunctionalization. Issue 8 (February 2016) - Chopin, Nicolas; Yanai, Hikaru; Iikawa, Shinya; Pilet, Guillaume; Bouillon, Jean‐Philippe; Medebielle, Maurice
Abstract: The synthesis of a series of γ‐ylidenetetronate derivatives is accomplished through a new aldolization/dehydration sequence.